New black fungus gnats (Diptera: Sciaridae) from Eastern Australia - Mohrig, Werner; Kauschke, Ellen; Broadley, Adam (Zootaxa, 2018)
The following 17 species are described as new for science: Austrosciara heterospinata sp. n., Aus. kalliesi sp. n., Aus. multispinulata sp. n., Aus. stockerae sp. n., Aus. trichovenosa sp. n., Bradysia chloroantennata sp. n., B. fuscovirgata sp. n., B. loudoni sp. n., B. macrotrichata sp. n., B. nigroantennata sp. n., B. parareflexa sp. n., Cratyna (Peyerimhoffia) subvagabunda sp. n., Euricrium (Austroeuricrium) australiensis sp. n., Phytosciara crocera sp. n., Pseudolycoriella latostylata sp. n., Psl. rubroalata sp. n., and Scatopsciara nigrothoracica sp. n. The following 4 species are new records for Australia: B. aspercera Mohrig, B. centidens Vilkamaa, Hippa & Mohrig (both from Papua New Guinea), B. gibbosa Vilkamaa, Hippa & Mohrig and Pseudolycoriella capillosa Vilkamaa, Hippa & Mohrig (both from New Caledonia). Euricrium australiensis sp. n. is the type species of the subgenus Austroeuricrium subgen. n. First detections of the species B. conjuncta (Skuse), B. exsequialis (Skuse), B. pernitida (Skuse) and B. pictipes (Skuse) were made after their description in the 19th century. One species was declared as a new synonym: B. centidens Vilkamaa, Hippa & Mohrig, 2012 = B. mutuata Mohrig, 2016 syn. n. Five species were excluded from the subgenus Peyerimhoffia. Four are newly combined in the genus Corynoptera, crassistylata group [C. sparsula (Shi & Huang) comb. n., C. brachypoda (Shi & Huang) comb. n., C. yunnana (Shi & Huang) comb. n., C. shennongjiana (Shi & Huang) comb. n.], one in Corynoptera s. str. [C. longiprojecta (Shi & Huang) comb. n.]. Corynoptera longiprojecta (Shi & Huang) is a junior synonym of Corynoptera diversicalcaria Mohrig, 2004 from Papua New Guinea.